UPAYA PENINGKATAN PENGETAHUAN APARAT DESA TENTANG MONOGRAFI DESA DI DESA ALU - Abubakar, Rahmah; Mayapada, Retno (Arunika: Jurnal Pengabdian Masyarakat, 2024)
Village monographs are a collection of data carried out by village and sub-district governments which are arranged systematically, completely, accurately, and integrated into government administration. Complete, accurate, and responsive information and data are important factors in development planning and community empowerment programs. Alu Village is located in Allu subdistrict, Polewali Mandar Regency, West Sulawesi. Information in the form of monographic data in Alu Village needs to be carried out optimally. Alu Village officials need to be given socialization and training on how to use technology, in this case, related to the preparation and visualization of monographic data, so that it can help maximize performance and have a good impact on village development. The aim of this socialization is to increase the knowledge of village officials about the importance of monographic data and utilize technology in compiling and visualizing monographic data as well as increasing the ability of village officials regarding data presentation techniques so that village monographic data can be more easily understood by users, both from the community and village officials. This activity was carried out using lecture methods. The socialization activity was attended by 15 participants. This activity was carried out well. In general, this activity succeeded in increasing the understanding of Alu Village officials, Polewali Mandar Regency regarding the preparation and visualization of monographic data.